Evaluation of participatory governance for enhancing quality of local governments: Towards a new model - Michael GALUKANDE-KIGANDA; Loraine Boitumelo TUMI MZINI (Smart Cities and Regional Development Journal)
Public participation in government programmes has gained prominence, the world over as it enhances democratization good governance and quality of governments. Involving the public in government activities is associated with improved efficiency, accountability, inclusiveness and quality public service provisioning. Different countries design varying types and forms of participatory governance structures with varying impacts on public management. Uganda is among the countries that for long embraced elaborate and universal participatory governance frameworks at both central and local government’s programmes.The primary objective of the study was to evaluate the participatory governance framework, so far as 1997 and its contribution to quality of local governments in Uganda. The empirical objectives were to evaluate participatory planning, budgeting and capacity of local councilors in managing local government policies.The study was based on a cross-sectional designed carried out in six selected districts in Central Uganda using both qualitative and quantitative approaches. Ninety questionnaires were administered to political leaders, technical officers, members of CSOs, and public to evaluate their opinions on the current forms of participatory governance. In addition, the study relied on oral interviews, literature review and field observations.Findings of the study revealed that indeed participatory governance framework had to some reasonable extent improved quality of local governments. Findings also revealed that voice and accountability, control of corruption and enhancing government effectiveness are vital factors for quality local governments. The study findings further revealed that participatory planning, budgeting and capacity of local councilors are important contributing factors to quality in local governments. A hybrid Local Government Participatory Governance Model was developed.The study recommended that central government develop local government-feasibility-assessment-guidelines to inform formation of new districts. There should also be regular policy trainings to local councilors toe empower them and to enhance capacity of accountability institutions and departments in local governments.